Testing of technical analysis on USD/JPY - Danilov, Evgenii; Vejmělek, Jan; Šíma, Ondřej; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
The main objective of this thesis is to create a successful Forex trading strategy based only on chart patterns as an instrument of the technical analysis method. To fulfill the aim of the work, it is devided into two parts. Part One describes theoretical aspects of Forex trading such as basic terms and principles and gives the reader an insight into evaluation methods used on the market. There is an introduction to the technical analysis and a detailed explanation of the instruments used in this method. Part Two is dedicated to practical aspects of the work. There is the strategy compiling and its subsequent testing and analysis. Testing is made on real historical data from 2016. As an underlying instrument, the USD/JPY pair was chosen. The main contribution of the bachelor thesis is a detailed description of the strategy building process. It is also tested if the strategy based on chart patterns may be successful without using indicators as a supporting instrument.
Vedoucí práce: Jan Vejmělek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses